2015
DOI: 10.1111/1471-0528.13447
|View full text |Cite
|
Sign up to set email alerts
|

Time to diagnosis of Type I or II invasive epithelial ovarian cancers: a multicentre observational study using patient questionnaire and primary care records

Abstract: ObjectiveTo compare time to diagnosis of the typically slow‐growing Type I (low‐grade serous, low‐grade endometrioid, mucinous, clear cell) and the more aggressive Type II (high‐grade serous, high‐grade endometrioid, undifferentiated, carcinosarcoma) invasive epithelial ovarian cancer (iEOC).DesignMulticentre observational study.SettingTen UK gynaecological oncology centres.PopulationWomen diagnosed with primary EOC between 2006 and 2008.MethodsSymptom data were collected before diagnosis using patient questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 37 publications
2
30
0
1
Order By: Relevance
“…The authors found no differences, but no analysis was performed on overall survival. 11 Finally, Nagle et al 12 interviewed 1318 patients to assess time to diagnosis and overall survival. They did not find any association, but did find that incidentally found cancers were more likely to be stage 1 or borderline tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found no differences, but no analysis was performed on overall survival. 11 Finally, Nagle et al 12 interviewed 1318 patients to assess time to diagnosis and overall survival. They did not find any association, but did find that incidentally found cancers were more likely to be stage 1 or borderline tumors.…”
Section: Discussionmentioning
confidence: 99%
“…They found no differences in time to presentation or diagnosis; however, no survival analysis was performed. 11 Nagle et al 12 used an interview model and correlated this to overall survival; similarly, they did not find any association with time to diagnosis. No study has correlated time to diagnosis based on medical record data to overall survival.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Of these, high-grade serous carcinoma is the most common, and accounts for > 50-60% of cases [4, 5]. Thus, most genome-wide analyses, including whole-exome sequencing, target this form of ovarian cancer [68].…”
Section: Introductionmentioning
confidence: 99%
“…Two distinct histotype subgroups exist and are defined as follows: type 1 (mucinous, low-grade serous, low-to moderate-grade endometrioid, clear cell) and type 2 (moderate-to high-grade serous, high-grade endometrioid, undifferentiated, malignant mixed mesodermal tumours). 10 Date of diagnosis was defined as the date a procedure was performed for the purposes of diagnosis (e.g., cytology, histology, blood work, imaging). Postal codes were used to identify residence at diagnosis and converted into income quintiles (stratified into urban and rural).…”
Section: Sources Of Datamentioning
confidence: 99%